LANDSLIDE SUSCEPTIBILITY ZONATION, KABILA BONE SUB-DISTRICT, BONE BOLANGO DISTRICT, GORONTALO PROVINCE - I Gede Sindu Pratama; Sri Maryati; Ronal Hutagalung (Geographica: Science and Education Journal, 2021)
The research area is administratively located in the Kabila Bone Sub-district, Bone Bolango District, Gorontalo Province which has an area of 143,51 km2. The purpose of the research is determine landslide susceptibility zonation of Kabila Bone  Sub-district , Bone Bolango District, Gorontalo Province. The method used in this research is geological survey method and analysis of geographic information system. The parameters used refers to Peraturan Menteri Pekerjaan Umum No. 22/PRT/M/2007, which includes of slope, soil condition, lithology, rainfall, slope water system, seismicity, and vegetation. The result of research show that Kabila Bone Sub-district consists of a zone with a low level of  susceptibility which has an area of 1258,76 ha, a zone with a medium level of  susceptibility which has an area of 4026,90 ha, and a zone with a high level of  susceptibility which has an area of 502,03 ha. Zones that have a high level of  susceptibility are distributed in several villages, namely Botubarani Village with an area of 117,92 ha, Huangobotu Village with an area of 89,35 ha, Bintalahe Village with an area of 64,22 ha, Oluhuta Village with an area of 119,98 ha, and Olele Village with an are of 104,01 ha.